Intraperitoneal hemorrhage secondary to ruptured omental artery aneurysm associated with polyarteritis nodosa: a case report - Mohamed H. El-Farra; Rayan Yahia; Aysenur Cetinkaya; Nahidh Hasaniya (Surgical Case Reports)
Abstract Background Polyarteritis nodsa (PAN) is a rare disease characterized by acute focal inflammatory damage to small and medium arteries. PAN complicated by ruptured aneurysm is an infrequent presentation with the most affected arteries being the renal and mesenteric arteries. Case presentation A 76-year-old female presented with a low-grade fever, generalized body aches, and abdominal pain. Investigation revealed intraperitoneal bleeding secondary to a ruptured and actively bleeding right omental artery aneurysm. Clinical manifestation, angiography and histology were consistent with PAN. Laparotomy was performed for stabilization and resection of the bleeding aneurysm followed by post operative steroids and cyclophosphamide. Patient was discharged in a stable condition. We reviewed seven cases found in the literature of omental artery aneurysm and rupture. Four cases were proceeded with laparotomy and aneurysm resection while three cases were proceeded with a less invasive approach of arterial embolization. Conclusions Omental artery aneurysm is a rare occurrence with even fewer reported cases associated with PAN. Of the seven reported cases, all patients were treated with a surgical intervention. In addition, PAN patients should be treated post-operatively with a course of steroids and cyclophosphamide.